Modelling mobile technology growth using diffusion models and Neural Networks. (30th October 2009) - Mukhopadhyay, Somnath; Bagchi, Kallol; Udo, Godwin J.
It is important for market planners and managers of Multi-National Enterprises (MNEs) to forecast global adoption of information technology for efficient market planning. This study builds two pure diffusion models, two popular time-series forecasting models, and one simple Neural Network (NN) model to predict mobile technology growth in 30 Organisation of European Council for Development (OECD) countries, the European Economic and Monetary Union (EMU) of the European Union (EU), and four non-OECD emerging nations. We compare the performances of all models on new samples. The results show that the NN model is superior to all other models.